A review on the engine performance and exhaust emission characteristics of diesel engines fueled with biodiesel blends - Damanik N.; Ong H.C.; Tong C.W.; Mahlia T.M.I.; Silitonga A.S. (Springer Verlag, 2023)
alternative fuel; biofuel; carbon monoxide; combustion; diesel engine; exhaust emission; oxide group; particulate matter; performance assessment; biofuel; carbon monoxide; gasoline; nitrogen oxide; analysis; chemistry; exhaust gas; Biofuels; Carbon Monoxide; Gasoline; Nitrogen Oxides; Vehicle Emissions